Refuge in a moving world : tracing refugee and migrant journeys across disciplines - Fiddian-Qasmiyeh, Elena, 1978- (UCL Press, 2020)
Refuge in a Moving World draws together over 30 contributions written from multiple disciplines to open up informed conversations about migration and displacement, including a particular focus on how people inhabit and negotiate everyday life in cities, towns, camps and informal settlements across the Middle East and North Africa, Southern and Eastern Africa, and Europe.